Prevalence of Bronchiolitis among Hospitalized Children less than Two Years in Babylon Province - Maha. A. Kadim1, Nuhad M. AL-Doori2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Bronchiolitis is one of viral lower respiratory tract infections that constitute a heavy burden to public health in the Pediatric population worldwide, which occurs most frequently before age 2 years in the winter and early spring months and most frequently induced by a viral infection (respiratory syncytial virus).Settings and Design: A survey descriptive study conducted in Babylon Province through-out the period of “1st January 2019 to 30 March 2019” (three) special hospitals of pediatrics.Method and Materials: Non-probability “purposive” sample consists of 3374 subjects, which collected through a review of patient records for (2016, 2017, 2018) in the statistical units in Babylon hospitals. The information of data was collected retrospectively through-out the special questionnaire obtained from the patient’s sheets in the statistical unit.Statistical analysis used: The data are coded and tested by the application (SPSS) through the descriptive and inferential analysis.Results: The analysis of the study indicated that the majority of the children (62.7%) were aged (1- 6) months old who lived in rural areas, the male percentage was higher than the female. In addition, the study indicated that the prevalence of bronchiolitis progressed during the last three years.Conclusions: The study concludes that the higher morbidity of bronchiolitis was in 2018, most of them admitted to the hospital in January months. Also, the duration of hospital stay was > 4 days.